Discovery of titin and its role in heart function and disease - Granzier, Henk L.; Labeit, Siegfried (Circulation research, 2025)
This review examines the giant elastic protein titin and its critical roles in heart function, both in health and disease, as discovered since its identification nearly 50 years ago. Encoded by the TTN (titin gene), titin has emerged as a major disease locus for cardiac disorders. Functionally, titin acts as a third myofilament type, connecting sarcomeric Z-disks and M-bands, and regulating myocardial passive stiffness and stretch sensing. Its I-band segment, which includes the N2B element and the PEVK (proline, glutamate, valine, and lysine-rich regions), serves as a viscoelastic spring, adjusting sarcomere length and force in response to cardiac stretch. The review details how alternative splicing of titin pre-mRNA produces different isoforms that greatly impact passive tension and cardiac function, under physiological and pathological conditions. Key posttranslational modifications, especially phosphorylation, play crucial roles in adjusting titin’s stiffness, allowing for rapid adaptation to changing hemodynamic demands. Abnormal titin modifications and dysregulation of isoforms are linked to cardiac diseases such as heart failure with preserved ejection fraction, where increased stiffness impairs diastolic function. In addition, the review discusses the importance of the A-band region of titin in setting thick filament length and enhancing Ca²+ sensitivity, contributing to the Frank-Starling Mechanism of the heart. TTN truncating variants are frequently associated with dilated cardiomyopathy, and the review outlines potential disease mechanisms, including haploinsufficiency, sarcomere disarray, and altered thick filament regulation. Variants in TTN have also been linked to conditions such as peripartum cardiomyopathy and chemotherapy-induced cardiomyopathy. Therapeutic avenues are explored, including targeting splicing factors such as RBM20 (RNA binding motif protein 20) to adjust isoform ratios or using engineered heart tissues to study disease mechanisms. Advances in genetic engineering, including CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats), offer promise for modifying TTN to treat titin-related cardiomyopathies. This comprehensive review highlights titin’s structural, mechanical, and signaling roles in heart function and the impact of TTN mutations on cardiac diseases.